A Randomized Controlled Trial of the Collaborative Assessment and Management of Suicidality versus Enhanced Care as Usual With Suicidal Soldiers. Issue 4 (2nd October 2017) - Jobes, David A.; Comtois, Katherine Anne; Gutierrez, Peter M.; Brenner, Lisa A.; Huh, David; Chalker, Samantha A.; Ruhe, Gretchen; Kerbrat, Amanda H.; Atkins, David C.; Jennings, Keith; Crumlish, Jennifer; Corona, Christopher D.; et al.
Abstract : Objective : This study describes a randomized controlled trial called "Operation Worth Living" (OWL) which compared the use of the Collaborative Assessment and Management of Suicidality (CAMS) to enhanced care as usual (E-CAU). We hypothesized that CAMS would be more effective than E-CAU for reducing suicidal ideation (SI) and suicide attempts (SA), along with secondary behavioral health and health care utilization markers for U.S. Army Soldier outpatients with significant SI (i.e., > 13 on Beck's Scale for Suicide Ideation). Method : Study participants were 148 Soldiers who presented to a military outpatient behavioral health clinic. There were 73 Soldiers in the experimental arm of the trial who received adherent CAMS; 75 Soldiers received E-CAU. Nine a-priori treatment outcomes (SI, past year SA, suicide-related emergency department (ED) admits, behavioral health-related ED admits, suicide-related inpatient psychiatric unit (IPU) days, behavioral health-related IPU days, mental health, psychiatric distress, resiliency) were measured through assessments at Baseline and at 1, 3, 6, and 12 months post-Baseline (with a 78% retention of intent-to-treat participants at 12 months). Results : Soldiers in both arms of the trial responded to study treatments in terms of all primary and secondary outcomes (effect sizes ranged from 0.63 to 12.04). CAMS participants were significantly less likely to have any suicidal thoughts by 3 months in comparison to those in E-CAU (Cohen's d = 0.93, p=.028). Conclusions : Soldiers receiving CAMS and E-CAU significantly improved post-treatment. Those who received CAMS were less likely to report SI at 3 months; further group differences were not otherwise seen.